2008
DOI: 10.1111/j.1524-475x.2007.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled delivery of bFGF to recipient bed enhances the vascularization and viability of an ischemic skin flap

Abstract: Therapeutic angiogenesis is a promising approach to treat ischemic skin flaps. We delivered basic fibroblast growth factor (bFGF) to the recipient bed of a rat dorsal skin flap by a drug delivery system with acidic gelatin hydrogel microspheres (AGHMs), and assessed augmentation of neovascularization and flap viability. An axial skin flap was elevated on the back of male Sprague-Dawley rats, and bFGF solution or bFGF-impregnated AGHMs were injected into the recipient bed. The dose of bFGF in the bFGF solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The need for experimental models of ischemic wounds is therefore compelling. Skin flaps represent a proven classical approach to induce ischemia (5,6,(21)(22)(23). In this study, the flap dimensions were optimized such that the tissue was ischemic but not necrotic.…”
Section: Discussionmentioning
confidence: 99%
“…The need for experimental models of ischemic wounds is therefore compelling. Skin flaps represent a proven classical approach to induce ischemia (5,6,(21)(22)(23). In this study, the flap dimensions were optimized such that the tissue was ischemic but not necrotic.…”
Section: Discussionmentioning
confidence: 99%
“…Using the re-epithelialized area as the numerator and the original width as the denominator and multiplying by 100 gives the percentage of the wound re-epithelialized (E/W) ϫ 100 ϭ percent re-epithelialization. Data are means Ϯ SD (n ϭ 3); *P Ͻ 0.05. classical approach to induce ischemia (14,27,28,37,60). In this study, the flap dimensions were optimized such that the tissue was ischemic but not necrotic.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we reported that sensory ES can induce greater release of VEGF on day 7 after incisional wounding [16]. It seems that FGF-2 plays some role in VEGF signaling and upregulation of VEGF expression [7,39]. Thus, according to results of the present study and those of our previous study, sensory ES, via an increase in expression of FGF-2 during the early phase of healing, may induce upregulation of VEGF during the proliferation phase of the healing process.…”
Section: Discussionmentioning
confidence: 99%